Дослідження двоїстої задачі оптимізації інвестиційного портфеля в нечітких умовах - Zaychenko, Yu.; Ovi, Nafas Agai Ag Gamish (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2011)
The dual problem of the investment portfolio optimization in fuzzy conditions is considered and investigated. The sufficient conditions of the mathematical model convexity of this problem are obtained and discussed. The results of experimental investigations of the solutions of the derect and dual problem of fuzzy portfolio optimization are presented.